Educational marketing in the conditions of development of the market of educational services in modern Ukraine - Poltorak, Volodymyr (Ukrainian Sociological Journal, 2015)
The article is devoted to the analysis of the topical problems of higher education in Ukraine, namely influence of the demographic crisis, sharp decrease in the number of secondary school graduates, and government’s methods of regulation of the educational market. Such topics as training provided by state and private higher educational institutions and contradictions between demands of national economy for specialists in particular fields and youths’ interest in those fields of the higher education that they deem to be optimal are discussed. Problems of applying educational marketing to regulation of the educational market are analyzed.